Exercising choice: The economic determinants of physical activity behaviour - Brown, H; Roberts, J (My University, 2011)
Lack of physical activity is a major contributing factor to the worldwide obesity epidemic, and to the overall burden of disease. The deindustrialisation of developed economies and move to more sedentary employment has impacted on the opportunities of working individuals to participate in physical activity. This can have negative effects on productivity and worker health potentially influencing economic growth. Thus, it is important to determine the factors influencing the frequency of participation in physical activity for employed individuals. This paper uses a modified time allocation framework to explore this issue. We use data from the first six waves of the Household Income and Labour Dynamics of Australia survey (HILDA). The analysis examines frequency of participation in physical activity using a generalised random effects ordered probit model. We control for non-parallel cut-points between the physical activity categories and individual heterogeneity, as well as exploring differences across gender. The results indicate that there is a time trade-off between non-market work, market work, and the frequency of physical activity participation. This effect is moderated by gender. For example, dependent children have a larger negative effect on the frequency of physical activity participation for women. Education and marriage have a larger negative effect on the frequency of participation for men. The findings suggests that policies which make exercise more convenient, and hence decrease the opportunity cost of exercise, will help to encourage more frequent participation in physical activity for working adults.
Keywords: Health -- Physical activity; Health; Health and wellbeing; Health; Physical activity; Health and wellbeing